2013
DOI: 10.1007/s12253-013-9634-0
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Nationwide Lymphoma Study in Lebanon: Incidence of Various Subtypes and Analysis of Associations with Viruses

Abstract: Incidence of various Hodgkin (HL) and non-Hodgkin lymphoma (NHL) subtypes and association with viruses in Lebanon are not known. We undertook a nationwide study of 272 patients diagnosed with lymphoma in 2007. HL comprised 32.7 % (n = 89) of cases while NHL represented 67.3 % (n = 183). Consistent with the literature, nodular sclerosis was the most predominant HL subtype (n = 57/89). Among NHL, B-cell NHL represented 88 % (n = 161/183), T-cell NHL 9 % (n = 17/183), whereas in 2.7 % it was not classifiable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…A review of other published studies from NAF/ME/IN (Castella et al , ; Almasri et al , ; Isikdogan et al , ; Abdel‐Fattah & Yassine, ; Sahni & Desai, ; Akhtar et al , ; Goldman et al , ; Ameen et al , ; Mozaheb et al , ; Yaqo et al , ; Arora et al , ; Otrock et al , ; Mondal et al , ) generally showed relative frequencies of NHL subtypes similar to our study (Table ). The most common lymphoma in all of these studies was DLBCL, ranging from 31% in Egypt (Abdel‐Fattah & Yassine, ) to 59% in the United Arab Emirates (UAE) (Castella et al , ), with most studies reporting a frequency above 40%.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A review of other published studies from NAF/ME/IN (Castella et al , ; Almasri et al , ; Isikdogan et al , ; Abdel‐Fattah & Yassine, ; Sahni & Desai, ; Akhtar et al , ; Goldman et al , ; Ameen et al , ; Mozaheb et al , ; Yaqo et al , ; Arora et al , ; Otrock et al , ; Mondal et al , ) generally showed relative frequencies of NHL subtypes similar to our study (Table ). The most common lymphoma in all of these studies was DLBCL, ranging from 31% in Egypt (Abdel‐Fattah & Yassine, ) to 59% in the United Arab Emirates (UAE) (Castella et al , ), with most studies reporting a frequency above 40%.…”
Section: Discussionmentioning
confidence: 87%
“…The frequency of CLL/SLL was lowest in UAE (1%) (Castella et al , ) and highest in Iran (23·9%) (Mozaheb et al , ). The frequency of T‐NHL ranged from 1·9% in Iran (Mozaheb et al , ) to 18·4% in Lebanon (Otrock et al , ) , and frequencies higher than 10% were reported from Jordan (Almasri et al , ), Saudi Arabia (Akhtar et al , ) and India (Sahni & Desai, ; Arora et al , ; Mondal et al , ). These highly variable findings point to the need for systematic, large‐scale studies such as this in order to better understand these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will be followed by non-Hodgkin disease with 20.0 cases per 100,000. A recent nationwide lymphoma study in Lebanon noted an increase in lymphomas worldwide over the past decade and argued for the need of large scale studies to assess the increasing rates [13]. Worldwide, an annual increase of 1-2% in non-Hodgkin lymphoma incidence has been noted, mostly in older people aged over 55 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…HL represented 32.7% of all cases of lymphoma diagnosed in Lebanon in 2007. In most patients IgG anti-Epstein-Barr virus were present, but serology for hepatitis C virus (HCV) was negative in 122 tested cases [6].…”
Section: Introductionmentioning
confidence: 99%